Tata Kelola Program Itsbat Nikah Terhadap Status Perkawinan yang Tidak Tercatat di Kota Sawahlunto - Riskita Fitria; Zulkarnaini (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
The governance of the implementation of the integrated marriage program for unregistered marriage status highlights the process of legalization for couples who have not registered their marriages by launching efforts to facilitate marriage registration for couples who were previously unregistered with an easier and integrated approach with this program. This study uses Sedarmayanti theory with four indicators, namely accountability, transparency, openness, and the rule of law. The method used in this study is a qualitative research method with data collection techniques, namely interviews, observations, and documentation. The results of this study show that the implementation of integrated marriage itsbat is very helpful to the community in obtaining legal legality, although it still faces challenges such as lack of budget in this program, lack of public understanding, and lack of access or news to this program so that it is needed between government institutions, religious courts, and the community to increase awareness and facilitate access to this program.